Penerapan Model Problem Based Learning untuk Meningkatkan Keaktifan dan Hasil Belajar IPA Siswa Kelas V - Alfitriatun Nurun Alfiah (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2017)
The purpose of this research is to increase the activeness and learning outcomes of the fifth grade students of SDN Karangmenggah Wonorejo Pasuruan. This study was designed using a classroom action research model of Kemmis and Mc. Teggart. Data collection techniques used were observation, interviews, and tests. The results showed that the Problem Based Learning learning model could increase activeness and learning outcomes in science subjects.